Róma vagy Bizánc? A két rítus találkozása a magyar keresztyénség első századaiban - Olga LUKÁCS (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2018)
Rome or Byzantium? The Encounter of the Two Rites in the First Centuries of Hungarian Christianity.